Pengembangan Sistem Informasi Pengelolaan Nilai Siswa Menggunakan Metode Human Centered Design (Studi Pada SMP Negeri 1 Gondanglegi) - Ahmad Maula Rifqi; Yusi Tyroni Mursityo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
SMP Negeri 1 Gondanglegi is a junior high school with a total teacher reaching 45 and the average number of students reaches 750 each year. The research at SMP Negeri 1 Gondanglegi was aimed to improve the business process of managing student grades to be more efficient and flexible in the working time and student report card printing process. The method used in this study was Human Centered Design (HCD). There are four stages in the HCD method is understand and specify context of use, specify user requirements, produce design solutions and evaluate the design against requirement. Results from this study was a web-based information system. The information system built has been carried out black-box testing which produces valid values ​​in all test cases. Then compatibility was used to test non-functional requirements with success on all browsers tested. In usability testing there are 3 aspects: effectiveness, efficiency and user satisfaction. The results of usability testing on the aspect of effectiveness of the average of all user groups is 98%. While on the average efficiency aspect the overall total efficiency aspects in the user group are 93%. Whereas in determining aspects of satisfaction using the PSSUQ questionnaire with an average score of all categories reaching 1.64. In the PSSUQ questionnaire it had the principle of lower score high usability, where if the score obtained is getting smaller then the usability is getting bigger.